2019
DOI: 10.1007/s42452-019-1550-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baffles shape on the flow patterns and power consumption in stirred vessels

Abstract: Effects of the baffles shape on the fluid velocities, flow patterns and power consumption in vessels agitated by a six blade Rushton turbine are explored in this paper. The curvature of baffles, their length, position and width are the main parameters under investigation. The study is carried out by using the Computational Fluid Dynamics tool, for a range of Reynolds number in the turbulent flow regime from 10 4 to 10 5. The comparison between the straight and curved baffles revealed that the curved shape allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Although the tangential velocity component dominated the flow in the vessel (results not shown), the impeller generated an axial outflow with trailing vortices interacting with the baffles and vessel wall, generating a recirculation loop in the region below the impeller. It is well‐established that baffling increases the turbulence level of any agitated vessels, promotes axial (top‐to‐bottom) recirculation, and thus reduces blend time (Foukrach & Ameur, 2019). However, the recirculation loop was found to be much weaker above the impeller, especially near the liquid surface, creating a region with significantly reduced fluid motion, which could be more difficult to homogenize especially in a full‐scale system.…”
Section: Resultsmentioning
confidence: 99%
“…Although the tangential velocity component dominated the flow in the vessel (results not shown), the impeller generated an axial outflow with trailing vortices interacting with the baffles and vessel wall, generating a recirculation loop in the region below the impeller. It is well‐established that baffling increases the turbulence level of any agitated vessels, promotes axial (top‐to‐bottom) recirculation, and thus reduces blend time (Foukrach & Ameur, 2019). However, the recirculation loop was found to be much weaker above the impeller, especially near the liquid surface, creating a region with significantly reduced fluid motion, which could be more difficult to homogenize especially in a full‐scale system.…”
Section: Resultsmentioning
confidence: 99%
“…Sirasitthichoke et al studied the macromixing of several types of single baffle (beavertail, D-type, H-type, finger-type, and fin-type baffles) in a retreat-blade impeller (RBI) system through experiments and simulations, and found that the beavertail baffle had the smallest power number. Foukrach studied the influence of parameters such as the curvature of the baffle on the velocity, flow pattern, and power consumption, and found that compared with the straight baffle, the curved baffle can produce a strong radial jet when the mid-height of curved baffles was located at almost the same level of impeller blades. For a multiphase system, Karcz and Mackiewicz studied the influence of the number, length, and installation mode of baffles on the suspension characteristics of self-floating particles, and their results confirmed the superiority of nonstandard baffles.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the most effective parameter on heat transfer is Reynolds number and baffle width and corner angle insignificant effect on Nusselt number. Foukrach and Ameur [18] studied the impact of the shape of the baffle on the flow characteristics numerically. The incompressible turbulent flow was simulated, and the optimum baffles were obtained.…”
Section: Introductionmentioning
confidence: 99%